2005
DOI: 10.1038/sj.onc.1209138
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of E-cadherin by hepatitis B virus X antigen in hepatocellullar carcinoma

Abstract: Hepatitis B virus (HBV)-encoded X antigen (HBxAg) contributes to the development of hepatocellular carcinoma (HCC). A frequent characteristic of HCC is reduced or absent expression of the cell adhesion protein, Ecadherin, although it is not known whether HBxAg plays a role. To address this, the levels of E-cadherin were determined in HBxAg-positive and -negative HepG2 cells in culture, and in tumor and surrounding nontumor liver from a panel of HBV carriers. The results showed an inverse relationship between H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 42 publications
(52 reference statements)
7
96
1
Order By: Relevance
“…Immunohistochemical studies of E-cadherin expression in HBV-related HCC have demonstrated significant downregulation of E-cadherin in the tumour tissue compared with adjacent non-tumour tissues (Yoshiura et al, 1995). Also, both in vitro and in vivo studies have suggested that HBx is implicated in the downregulation of E-cadherin (Arzumanyan et al, 2012;Lee et al, 2005;Liu et al, 2006). Consistently, the present study showed that HBx could induce EMT by downregulating levels of E-cadherin in hepatoma cells.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Immunohistochemical studies of E-cadherin expression in HBV-related HCC have demonstrated significant downregulation of E-cadherin in the tumour tissue compared with adjacent non-tumour tissues (Yoshiura et al, 1995). Also, both in vitro and in vivo studies have suggested that HBx is implicated in the downregulation of E-cadherin (Arzumanyan et al, 2012;Lee et al, 2005;Liu et al, 2006). Consistently, the present study showed that HBx could induce EMT by downregulating levels of E-cadherin in hepatoma cells.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, several reports have provided direct evidence for a role of HBx in the downregulation of E-cadherin (Arzumanyan et al, 2012;Lee et al, 2005;Liu et al, 2006). Two different mechanisms can be considered for the repression of E-cadherin expression by HBx in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…HBx may be able to induce an EMT phenotype in hepatoma cells, with decreased E-cadherin expression levels as well as an upregulation of vimentin and N-cadherin (29). In addition, β-catenin is primarily observed in the cytoplasm and nuclei of HBx-transfected cells (30). Furthermore, HBx has been demonstrated to induce EMT in human hepatoma cells by activating proto-oncogene tyrosine-protein kinase (c-Src) (29), or by modulating the signal transducer and activator of transcription (STAT) 3 signaling pathway in order to activate Twist (31).…”
Section: The Proteins Associated With the Cytoskeleton That Are Deregmentioning
confidence: 99%
“…The latter is of particular importance because suppression of the cell adhesion protein, E-cadherin, is a hallmark of EMT, which is important to the pathogenesis of CLD and HCC. The importance of suppressed E-cadherin expression is further underscored by the findings that this occurs by DNA methylation of the E-cadherin promoter (Lee et al, 2005;Liu et al, 2006), by the inhibition miR-373 expression by HBx, and by HBx mediated stimulation of histone deacetylase (HDAC) at the E-cadherin promoter (Arzumanyan et al, 2011). Independent of the mechanism involved, suppression of E-cadherin has important ramifications upon -catenin.…”
Section: Elevation Of -Catenin and Suppression Of E-cadherinmentioning
confidence: 99%
“…The finding that the activation of wild type -catenin was associated with URG11 and URG7 (Pan et al, 2007), underscores the importance of this activation in hepatocarcinogenesis. Moreover, -catenin appears to be stabilized by a number of mechanisms, including trans-activation of the -catenin promoter Pan et al, 2007), inhibition of proteasomal degradation (Cui et al, 2006;Zhang et al, 2000), and suppression of E-cadherin expression (Arzumanyan et al, 2011;Lee et al, 2005;Liu et al, 2006) (Figure 2). The latter is of particular importance because suppression of the cell adhesion protein, E-cadherin, is a hallmark of EMT, which is important to the pathogenesis of CLD and HCC.…”
Section: Elevation Of -Catenin and Suppression Of E-cadherinmentioning
confidence: 99%